2011
DOI: 10.1080/1745039x.2011.559722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding isolates of anaerobic fungusNeocallimastixsp. CF 17 on growth rate and fibre digestion in buffalo calves

Abstract: In this investigation, the effects of feeding encapsulated cells (rhizomycelia and zoospores) of a fibrolytic isolate from an anaerobic fungus (Neocallimastix sp. CF 17) on nutrient digestion, ruminal fermentation, microbial populations, enzyme profile and growth performance were evaluated in buffaloes. In three in vitro studies, the true digestibility of wheat straw was increased after addition of CF 17 to buffalo rumen fluid (p < 0.05). In Exp. 1, three groups of six buffaloes each (initial BW [body weight] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
(15 reference statements)
0
15
0
1
Order By: Relevance
“…Therefore, the high abundance of active rumen fungi in low-RFI steers may provide increased energy to hosts from the fermentation of structural polysaccharides, leading to a high feed efficiency. As an indirect proof, it has been demonstrated that inclusion of cultures of anaerobic fungi in the diets of various ruminants improved feed intake, animal growth rate, feed efficiency, and milk production (Lee et al, 2000;Saxena et al, 2010;Paul et al, 2011).…”
Section: Effect Of Residual Feed Intake On the Rumen Eukaryotic Micromentioning
confidence: 99%
“…Therefore, the high abundance of active rumen fungi in low-RFI steers may provide increased energy to hosts from the fermentation of structural polysaccharides, leading to a high feed efficiency. As an indirect proof, it has been demonstrated that inclusion of cultures of anaerobic fungi in the diets of various ruminants improved feed intake, animal growth rate, feed efficiency, and milk production (Lee et al, 2000;Saxena et al, 2010;Paul et al, 2011).…”
Section: Effect Of Residual Feed Intake On the Rumen Eukaryotic Micromentioning
confidence: 99%
“…The application of anaerobic fungi as a direct‐fed microbial supplement has been investigated, in both ruminant and nonruminant livestock production, as a means to improve utilisation of low‐quality forages. Inclusion of cultures of anaerobic fungi in the diets of various ruminants has been investigated and demonstrated to improve feed intake, animal growth rate, feed efficiency and milk production (Lee et al ., ; Dey et al ., ; Paul et al ., , ; Tripathi et al ., ; Samanta et al ., ; Sehgal et al ., ; Mamen et al ., ; Saxena et al ., ; Gao et al ., ). The benefits observed being even more marked in young ruminants (Theodorou et al ., ; Sehgal et al ., ) and sheep devoid of anaerobic fungi (Elliott et al ., ; Gordon & Phillips, ).…”
Section: Biotechnological Applicationsmentioning
confidence: 99%
“…The anaerobic gut fungi (AGF) represent a basal fungal phylum (Neocallimastigomycota) that resides in the herbivorous gut and plays an important role in enhancing plant biomass metabolism by the host animals ( Gruninger et al, 2014 ). The AGF have multiple potential biotechnological applications such as a source of lignocellulolytic enzymes ( Cheng et al, 2014 ; Kwon et al, 2016 ; Lee et al, 2015 ; Morrison, Elshahed & Youssef, 2016 ; Wang, Chen & Hseu, 2014 ; Wei et al, 2016a ; Wei et al, 2016b ), direct utilization of AGF strains for sugar extraction from plant biomass in enzyme-free biofuel production schemes ( Ranganathan et al, 2017 ), additives to biogas production reactors ( Nkemka et al, 2015 ; Procházka et al, 2012 ), and feed additives for livestock ( Dey et al, 2004 ; Lee, Ha & Cheng, 2000 ; Paul et al, 2011 ; Paul et al, 2004 ; Saxena et al, 2010 ; Sehgal et al, 2008 ; Tripathi et al, 2007 ). However, the strict anaerobic nature of AGF renders genetic manipulation procedures involving plating and colony selection extremely cumbersome.…”
Section: Introductionmentioning
confidence: 99%